2021
DOI: 10.1080/14670100.2021.1948716
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported music perception is related to quality of life and self-reported hearing abilities in cochlear implant users

Abstract: Objectives: To investigate the relationship between self-reported music perception and appreciation and (1) quality of life (QoL), and (2) self-assessed hearing ability in 98 post-lingually deafened cochlear implant (CI) users with a wide age range. Methods: Participants filled three questionnaires: (1) the Dutch Musical Background Questionnaire (DMBQ), which measures the music listening habits, the quality of the sound of music and the selfassessed perception of elements of music; (2) the Nijmegen Cochlear Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 80 publications
0
18
0
Order By: Relevance
“…Moreover, the acoustic manipulation in vocoded conditions may have distanced recognition of the content from the actual emotional experience, in particular for NH participants who are not used to listening to music with reduced spectrotemporal content. Our investigation thus is limited to the recognition of intended emotional content of music by the composer/performers, also with reduced spectrotemporal content, can generally contribute to overall music listening pleasure and experienced emotion (e.g., Sachs et al, 2015;Fuller et al, 2019Fuller et al, , 2021. Future studies could moreover explore the perceived/expressed emotion judgements with either open choice responses or more fine-grained response options.…”
Section: Limitations To the Current Paradigmmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the acoustic manipulation in vocoded conditions may have distanced recognition of the content from the actual emotional experience, in particular for NH participants who are not used to listening to music with reduced spectrotemporal content. Our investigation thus is limited to the recognition of intended emotional content of music by the composer/performers, also with reduced spectrotemporal content, can generally contribute to overall music listening pleasure and experienced emotion (e.g., Sachs et al, 2015;Fuller et al, 2019Fuller et al, , 2021. Future studies could moreover explore the perceived/expressed emotion judgements with either open choice responses or more fine-grained response options.…”
Section: Limitations To the Current Paradigmmentioning
confidence: 99%
“…While CIs partially restore hearing, the spectro-temporal details of the sounds transmitted are reduced compared to normal hearing (NH) (for a review of relevant factors related to electric stimulation of the nerve, the nerve-electrode interface, and physiological/clinical aspects, see Başkent et al, 2016). Thus while music 1 enjoyment has been reported to contribute to quality of life in CI users (Fuller et al, 2021; Lassaletta et al, 2008), the difficulties in hearing and appreciating music still persist within this population (e.g., Caldwell et al, 2017; Fuller et al, 2019; Gfeller et al, 2000; Lassaletta et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…They found that many of these children could distinguish tones and semitones on their instruments, primarily through the listening skills they have acquired by training themselves to interpret the sounds they heard through their implants. According to Fuller et al (62), their findings may imply that music education programs and/or device enhancements that improve music perception can improve QoL and hearing ability. In the light of this information, based on our study, differences in performance in individuals with CI can be examined by evaluation before and after music education with the MPT.…”
Section: Discussionmentioning
confidence: 99%
“…With the significant advancements achieved in cochlear implant (CI) technology in terms of speech perception, it is understandable that many current CI users wish to be able to listen to music. Furthermore, because music has played a vital role in many of these patients’ cultural and social lives prior to deafness, the promise of regaining music enjoyment is a major motivator for CI candidates ( Fuller et al, 2021 ; Gfeller et al, 2000 ). This is confirmed by self-reports stating that music is the second most significant stimulus for CI users after speech ( Gfeller et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another reported deficit is the reduced ability to discern dynamics or intensity in music, which is ascribed to the high level of compression in the CI signal ( Limb & Roy, 2014 ). Thus, for most CI users the music experience is unsatisfying, leading to little or no music enjoyment ( Fuller et al, 2021 ; Mirza et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%